ANALISIS DAYA DUKUNG TIANG PANCANG STEEL PIPE PILE BERDASARKAN DATA KALENDERING DAN PDA TEST (Studi Kasus: Project Strengthening Jetty 1 & Jetty 2 PLH Existing, Desa Paring Lahung, Kec. Montallat, Kab. Barito Utara, Kalimantan Tengah) - Kukuh Kurniawan Dwi Sungkono; Arbianto, Reki; Wijayanti, Paska; Prasetyo, Erwin Aji; Kurniawan, Rizal (Jurnal Teknik Sipil dan Arsitektur, 2025)
In the field of construction, particularly in geotechnical engineering, uncertainties in foundation design approaches are frequently encountered. Geotechnical uncertainties, especially in foundation design, pose complex challenges due to the heterogeneous nature of soil and data limitations. Dynamic load testing on pile foundations is an alternative method to static load testing in geotechnical engineering for evaluating pile capacity and behavior. The results of this analysis will be compared to the design capacity of pile foundations in the breasting dolphin structure. This study on a breasting dolphin structure utilizing Steel Pipe Pile (SPP) foundations with a diameter 610 mm. PDA tests were conducted on piles at points G6-23, G7-33, G7-38, and G8-46. The study begins with a literature review to comprehend methods and theories related to pile capacity analysis based on calendaring and PDA testing. Calendaring data were analyzed using empirical methods such as the Hiley Formula to estimate the dynamic bearing capacity of each pile. The pile capacity calculated using the Hiley Formula is generally higher than the results obtained from the Case Method and CAPWAP Analysis. The relationship between pile capacity based on the Hiley Formula (calendaring) and the Case Method (PDA test) yielded a linear regression equation of y = 1.0785x - 983.07 with R² = 0.2385, indicating a weak correlation. Meanwhile, the relationship between pile capacity from the Hiley Formula (calendaring) and CAPWAP Analysis (PDA test) resulted in a linear regression equation of y = -0.006x + 2909.8 with R² = 1×10?¹, indicating almost no linear correlation between the two.